The Effect of Body Mass Index on Treatment Outcomes in Patients with Metastatic Non-Small Cell Lung Cancer Treated with Platinum-Based Therapy. (14th September 2021) - Sakin, Aysegul; Sahin, Suleyman; Mustafa atci, Muhammed; Yasar, Nurgul; Demir, Cumhur; Geredeli, Caglayan; Sakin, Abdullah; Cihan, Sener
Abstract: To investigate the effect of body mass index(BMI) on treatment outcomes and side-effect profile in metastatic non-small cell lung cancer(NSCLC) patients receiving platinum-based chemotherapy(ChT) in the first-line setting. This was a retrospective analysis of 233 NSCLC patients who were treated and followed up from 2008 through 2018. NSCLC patients who had metastatic disease at the time of diagnosis and were treated with platinum-based ChT in the first-line setting were included. The patients were divided into 2 groups based on the BMI as follows; BMI < 25 kg/m 2 and BMI ≥ 25 kg/m 2 . This retrospective analysis enrolled 233 patients, 35 (15.0%) of whom were female. The BMI in 132 patients (56.2%) was < 25 kg/m 2 . The median age was 58 years (range, 21-90). Median progression-free survival(PFS) was 7 mo, in the patients with BMI ≥ 25 kg/m 2 compared to 5.0 mo, in those with BMI < 25 kg/m 2 ( p  = 0.032), with corresponding median overall survival(OS) durations of 12 vs. 9 mo, ( p  = 0.003). In multivariate analysis, ECOG PS 2, grade III histology, and brain or bone metastasis negatively affected OS, whereas BMI ≥ 25 kg/m 2 positively affected OS. A high BMI prior to therapy in patients with NSCLC treated with platinum-based ChT in the first-line setting was associated with more favorable PFS and OS.